2021
DOI: 10.1063/5.0025884
|View full text |Cite
|
Sign up to set email alerts
|

High-responsivity PtSe2 photodetector enhanced by photogating effect

Abstract: Platinum diselenide (PtSe2), a recently rediscovered two-dimensional transition metal dichalcogenide, has attracted immense attention in the optoelectronic field due to its tunable bandgap, ultrastability, and high electron mobility. However, the applications of PtSe2 photodetectors are seriously restricted by their low responsivity. In this work, a high-responsivity (5 × 104 A/W) PtSe2 photodetector is obtained by exploiting a photogating effect; this is induced by the hole-trapping states, which are attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…
layer-modulated magnetism and robust stability in air. These properties make it a promising candidate in various fields like electronics, [1][2][3][4][5] optoelectronics, [6][7][8][9][10][11][12][13] spintronics, [14] catalysis, [15] micro-electromechanics, [16] and sensing. [6,17,18] Monolayer or few-layer PtSe 2 can be synthesized by different methods, such as direct selenization of Pt films at a low temperature (≤400 °C), [3,4,6,8,19] which makes it scalable and compatible with current silicon chip fabrication technology, molecular beam epitaxy (MBE), [16,20,21] chemical vapor deposition (CVD), [5,22] and chemical vapor transport (CVT).
…”
mentioning
confidence: 99%
“…
layer-modulated magnetism and robust stability in air. These properties make it a promising candidate in various fields like electronics, [1][2][3][4][5] optoelectronics, [6][7][8][9][10][11][12][13] spintronics, [14] catalysis, [15] micro-electromechanics, [16] and sensing. [6,17,18] Monolayer or few-layer PtSe 2 can be synthesized by different methods, such as direct selenization of Pt films at a low temperature (≤400 °C), [3,4,6,8,19] which makes it scalable and compatible with current silicon chip fabrication technology, molecular beam epitaxy (MBE), [16,20,21] chemical vapor deposition (CVD), [5,22] and chemical vapor transport (CVT).
…”
mentioning
confidence: 99%
“…This phenomenon is different from the previous photoresponse, where the illumination could bring about the rise of the SS value. , It might be attributed to the negative photoresponse effect which has different interaction mechanisms and tunes the effective capacitance during the light illumination. Recently, it was also reported that the ambipolar PtSe 2 has positive and negative photoconductive effects under light illumination, where the photogating effect induced by the hole-trapping tunes the carrier . In this study, the negative photoresponse effect is owing to the desorption of negative ions (C 2 F 6 NO 4 S 2 – ) and photogating effect, which play different roles in electron and hole branch.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is different from the previously reported photoresponse of PtSe 2 and WSe 2 ambipolar phototransistors, where both the electron branch and hole branch shift. 31,34,35 Therefore, the current phenomenon could be triggered by the ion-gel film, which will be discussed later. To quantify the effect of the illumination on the threshold voltage, the shifting of the threshold voltage is normalized by its illumination power density.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[31][32][33] The novel properties revealed by these studies make 2D PtSe 2 an attractive material for many applications. In particular, recent investigations have demonstrated integration of 2D PtSe 2 in various devices with high performance, such as field-effect transistors, [15,29] photovoltaic devices, [11] photodetectors [11,15,27,[34][35][36] with mid-infrared spectral range [17,18,37] and high speed, [38,39] ultrathin meta-optical devices, [40] gas [11] and pressure sensors, [41] and catalysis devices. [7,13,42] In these applications, the dynamical properties of photocarriers often play a key role in determining the device performance.…”
Section: Introductionmentioning
confidence: 99%